Polysaccharides derived from Astragalus membranaceus and Glycyrrhiza uralensis improve growth performance of broilers by enhancing intestinal health and modulating gut microbiota - Yingying Qiao; Changzhong Liu; Yongpeng Guo; Wei Zhang; Weibing Guo; Kyselov Oleksandr; Zhixiang Wang (Poultry Science, 2022)
ABSTRACT: This study was conducted to investigate the effects of dietary supplementation of polysaccharides derived from Astragalus membranaceus and Glycyrrhiza uralensis on growth performance, intestinal health, and gut microbiota composition in broilers. A total of 480 one-day-old male Arbor Acres broilers were randomly divided into 4 treatments with 6 replicates comprising 20 broilers each. Treatments included: basal diet without antibiotics (CON); basal diet supplemented with 500 mg/kg terramycin calcium (ANT); basal diet supplemented with 300 mg/kg Astragalus membranaceus polysaccharides (APS); and basal diet supplemented with 150 mg/kg Glycyrrhiza uralensis polysaccharides (GPS). The results showed that ANT, AP,S and GPS supplementation significantly increased average daily gain (ADG) and decreased feed conversion ratio (FCR) of broilers from 1 to 42 d of age. At 42 d, serum immunoglobulin A (IgA), immunoglobulin M (IgM) and immunoglobulin G (IgG) levels of the APS and GPS group were notably higher than those of the CON group, while serum levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6) as well as diamine oxidase (DAO) activity in the APS and GPS group were obviously decreased. Moreover, diets supplemented with APS and GPS could significantly increase villus height (VH) and the ratio of villus height to crypt depth (VH/CD) and remarkably upregulated occludin, claudin-1 and mucin-2 (MUC2) mRNA expression in duodenum, jejunum, and ileum of broilers. In addition, 16S rRNA gene sequencing revealed that APS and GPS supplementation altered cecal microbial diversity and composition in broilers. Higher Shannon index was observed in the APS and GPS group compared with the CON group, while GPS supplementation could also increase Chao1 index and Observed species. The result of Principal coordinate analysis (PCoA) showed that microbial community in the CON, ANT, APS, and GPS group clustered separately. Notably, both APS and GPS supplementation significantly decreased the abundance of Bacteroidetes, Bacteroides, Faecalibacterium, Desulfovibrio, and Butyricicoccus, while increased the abundance of Firmicutes, Prevotella, Parabacteroides, Ruminococcus, and Alistipes. The correlation analysis showed that the changes in cecal microbial composition induced by dietary APS and GPS supplementation were closely associated with the alteration of the phenotype of broilers including ADG, FCR, TNF-α, IL-1β, IL-6, IgA, IgG, DAO, Occludin, Claudin-1, ZO-1, and MUC2. In conclusion, polysaccharides derived from Astragalus membranaceus and Glycyrrhiza uralensis could improve growth performance of broilers by enhancing intestinal health and modulating gut microbiota.